2012
DOI: 10.1139/y2012-130
|View full text |Cite
|
Sign up to set email alerts
|

CB1 and CB2 contribute to antinociceptive and anti-inflammatory effects of electroacupuncture on experimental arthritis of the rat temporomandibular joint

Abstract: Electroacupuncture (EA) and cannabinoids have been reported to have anti-inflammatory and antinociceptive effects in animal models of arthritis. Male Wistar rats were injected with saline or zymosan (2 mg) into the temporomandibular joint (TMJ). EA (10 Hz, 30 min) was performed 2 h after or 1 h before zymosan administration. AM251 or AM630 (3 mg/kg, i.p.)were administered before EA treatment. Mechanical hypernociception was accessed after zymosan administration. Rats were sacrificed 6 h after zymosan administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 45 publications
2
23
0
Order By: Relevance
“…However, because of this large number of expressed GPCRs, we focused on the 30 most highly expressed GPCRs (Figure 3, Ref. [ 47 61 ]).…”
Section: Resultsmentioning
confidence: 99%
“…However, because of this large number of expressed GPCRs, we focused on the 30 most highly expressed GPCRs (Figure 3, Ref. [ 47 61 ]).…”
Section: Resultsmentioning
confidence: 99%
“…NF- κ B locates in the nucleus, and CB2 is mainly expressed in the cell membrane and cytoplasm [ 28 , 29 ]; thus we infer that THC may activate CB2 receptors expressed in the cell membrane and cytoplasm of MG-63 cells and then inhibit NF- κ B expression to reduce the inflammatory factors release from the MG-63 cells exposed to LPS. Similarly, Gondim et al reported that CB2 is involved in electroacupuncture- (EA-) induced anti-inflammatory effects in a rat model of arthritis [ 30 ]. And Zarruk et al reported that the activation of microglial CB2 receptor brings about neuroprotection against brain ischemic injury by decreasing the proinflammatory cytokines release in mice [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The endocannabinoid system primarily consists of two types of receptors, cannabinoid CB1 and CB2 receptors. By employing AM251 and AM630 to block CB1 and CB2 receptors, respectively, Gondim et al demonstrated that both receptor types mediate the anti-nociceptive and anti-inflammatory effects of EDN [175]. However, inflamed tissue has been shown to express 10-100 times the number of CB2 receptors compared to CB1 receptor mRNA, suggesting that EDN may act primarily through CB2 receptors [176,177].…”
Section: The Role Of the Endocannabinoid System In Dry Needling-mediamentioning
confidence: 99%